Electrosynthesis of (hetero)aryl nitriles from α-imino-oxy acids via oxidative decarboxylation/N–O cleavage. Issue 64 (21st July 2022) - Lin, Hui-Shan; Chen, Shu-Jun; Huang, Jing-Mei
Abstract : The electrochemical decarboxylation/N–O bond cleavage of α-imino-oxy acids was achieved to build up (hetero)aryl nitriles via iminyl radicals. Abstract : A new method for the synthesis of (hetero)aryl nitriles via iminyl radicals has been developed through the electrochemical oxidative decarboxylation of α-imino-oxy acids. This protocol provides an efficient approach to nitriles with a broad range of functional-group tolerance under ambient conditions and can be applied for one-pot gram-scale synthesis.